An ultrasensitive sandwich immunoassay with a glucometer readout for portable and quantitative detection of Cronobacter sakazakii. Issue 44 (3rd November 2017) - Ye, Lingxian; Zhao, Guangying; Dou, Wenchao
Abstract : A new immunoassay for the detection of C. sakazakii was developed using PGM, antibodies and glucose oxidase coated silica nanoparticles and immune magnetic nanoparticles. Abstract : Developing portable and low-cost methods for quantitative detection of Cronobacter sakazakii ( C. sakazakii ) from powdered infant formula plays a significant role in controlling and preventing a range of serious neonatal infections. Here, we reported a novel methodology for C. sakazakii detection using a low-cost, simple, and widely accessible personal glucose meter (PGM) as the readout. The electrochemical immunoassay strategy was based on antibody and glucose oxidase coated silica nanoparticles (SiNP–GOX –IgG) and antibody functionalized silica-coated magnetic nanoparticles (MNP–IgG). In the process of detecting a positive sample, a sandwich immunocomplex was formed between the MNP–IgG, C. sakazakii and SiNP–GOX –IgG. Then, the above sandwich composites were dispersed in glucose solution, and the concentration of glucose was measured using the PGM. Under optimal conditions, a linear relationship between the decrease of glucose concentration and the logarithm of C. sakazakii concentration was obtained in the concentration range from 9.0 × 10 2 to 9.0 × 10 7 CFU mL −1 with a detection limit of 4.2 × 10 1 CFU mL −1 (S/N = 3). This simple immunoassay holds great potential as an efficient, sensitive and selective point-of-care testing (POCT) tool for C. sakazakii detection.